THE IMPACT OF MANUAL, PSYCHOLOGICAL INTERVENTION AND THE IMPLEMENTATION OF TRE-EXERCISES ON THE STATE OF ANXIETY OF ATO PARTICIPANTS WHO WERE ON A SPA TREATMENT - Gavlovsky, A.D.; Golovanova, I.A.; Strashko, E.U. (World of Medicine and Biology, 2019)
The purpose of this study was to determine the influence of manual, psychological intervention and TRE exercises on the anxiety state of ATO participants who were on sanatorium-resort treatment in a private joint-stock company of medical and health institutions “Mirgorodkurort”. In the process of manual intervention, coupled with verbalization of the problem, the fastest therapeutic effect is achieved. With anxiety, depression, the breathing pattern is disturbed in the direction of exhalation reduction, the body is constantly in a state of background stress disturbance, which affects both the physiological processes and the emotional-behavioral aspect of life. Therefore, to relieve anxiety, Dr. David Bersely proposed a special technique that includes exercises to relieve tension, stress and traumatic experience Tension, Stress and Trauma Releasing Exercises (TRE), which consist of seven exercises that are used to stimulate neurogenic tremor.